Akomodasi Komunikasi Antarbudaya (Etnis Jawa Dengan Etnis Minang) - Nadila Opi Prathita Sari; Turnomo Rahardjo (Interaksi Online, 2019)
Different cultural values can cause several problems during the interaction process. The case raised was the interaction of the Minang and Javanese ethnic groups. Ethnic Minang who studied in Semarang opened intercultural meetings, especially with host culture. The values and norms of Minang and Javanese cultural backgrounds have conflicting differences, which can even cause problems that lead to conflict. This study aims to find out what are the obstacles experienced when interacting and the forms of efforts made by strangers and host culture in accommodating each other. This study uses a phenomenological approach that is used to understand a phenomenon based on the perspective of the informant, this is related to the ongoing interaction between ethnic Minang and Javanese with the main focus of accommodation with each other. The theory used is the Theory of Communication Accommodation and Interaction Adaptation Theory which serves to explain the constraints and forms of accommodation efforts undertaken by ethnic Minang and Javanese. In this study used in-depth interview techniques that were used to four informants with a Minang cultural background and four informants with a Javanese cultural background. The results of the study are the constraints of interaction experienced by Javanese ethnic informants and Minang ethnic informants on speech style, differences in cultural values, and lack of information and knowledge about the culture of the other person. Accommodation efforts carried out by each ethnic Minang individual are diverse, some are converging and divergent. In addition, ethnic Javanese individuals also make accommodations by asking for help from a third person or friend to help him communicate with strangers.